Wajcman, Judy (2015). Pressed for Time: The Acceleration of Life in Digital Capitalism - Delclòs Alió, Xavier (Documents d’Anàlisi Geogràfica, 2017)
Wajcman, Judy (2015) Pressed for Time: The Acceleration of Life in Digital Capitalism Chicago i Londres: The University of Chicago Press, 215 p. ISBN 978-0-226-19647-3